Advertising support in healthcare settings for survivors of sexual violence: findings from a population-based survey in England - Aliyu Abubakar; Jonathan D. C. Ross; Rachel J. Caswell (Frontiers in Reproductive Health)
IntroductionSexual violence (SV) is common, but accessing appropriate support is frequently a challenge. Understanding how best to advertise healthcare support after SV could potentially improve access and long-term outcomes. This study investigates factors associated with increasing the visibility of advertisements for SV support in healthcare settings, and variations in the relevance of advertisements to different population sub-groups.MethodsAn online, population-based survey was conducted in England. The survey collected demographic data, history of whether they had seen SV support information and its perceived relevance.ResultsOverall, 2,007 respondents aged 18 years and above completed the survey. On multivariate analysis, younger age groups were significantly more likely to report seeing SV support advertisements compared to those aged 55 or older—individuals aged 18–24 years (AOR = 2.23, 95% CI = 1.36–3.65) and 25–34 years (AOR = 2.26, 95% CI = 1.43–3.57). Ethnicity and prior experience of SV were also significant predictors, with White respondents more likely to have seen the advertisements (AOR = 5.52, 95% CI = 1.81–16.85), as were those with a history of SV (AOR = 1.66, 95% CI = 1.34–2.05). Respondents aged 18–24 years (AOR = 3.29, 95% CI = 1.80–6.04) and 25–34 years (AOR = 2.32, 95% CI = 1.34–4.04) reported SV support information to be more relevant to them than those aged 55 or older, as did individuals with a history of SV (AOR = 1.82, 95% CI = 1.42–2.33).ConclusionsThe findings suggest younger people and those of White ethnicity and with a history of SV are more likely to see SV support information and perceive it as relevant. Advertising strategies targeting high-risk populations are essential to ensure equitable access to care.